Multigenerational Workforce Management Strategy in the Digital Era - Dharta, Firdaus Yuni; Guilin, Xie; Karliena, Yayuk; Butarbutar, Marisi; Diantoro, Eman (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
The growing concern over employee productivity and job satisfaction has led organizations to focus on welfare programs as a strategic tool. In many companies, these programs are designed to enhance employees’ well-being, which is expected to boost productivity and job satisfaction. However, the effectiveness of these programs remains a topic of debate. This research examines employee welfare programs’ impact on productivity and job satisfaction within various organizational settings. The study utilizes a quantitative approach, employing surveys and questionnaires distributed to 200 employees from diverse industries. Data were analyzed using statistical methods, particularly regression analysis, to determine the correlation between the presence of welfare programs and improvements in productivity and job satisfaction. The findings reveal that companies offering comprehensive welfare programs, such as health benefits, flexible working hours, and professional development opportunities, see significant improvements in employee productivity and job satisfaction. Moreover, employees who feel supported by these programs are likelier to exhibit higher organizational engagement and commitment. In conclusion, welfare programs play a crucial role in enhancing not only productivity but also the overall job satisfaction of employees. Organizations are encouraged to invest in such programs as a long-term strategy for workforce development and retention.